Strengthening Honesty Character in Early Childhood Through Islamic Religious Education: A Qualitative Case Study from Indonesia - Hasmi Hasmi; Raya Mangsi; Suredah Hamid; St. Warda Hanafie Das; Muhammad Naim (CV. Gerasi Insan Nusantara, 2026)
Honesty is one of the fundamental moral values that should be cultivated during early childhood, as this developmental stage plays a crucial role in shaping lifelong character. Although Islamic Religious Education (IRE) has long been recognized as an important medium for character development, empirical evidence explaining how IRE contributes to fostering honesty among young children within authentic educational settings remains limited. This study addresses this gap by examining the implementation of IRE and its contribution to honesty character formation in an Islamic kindergarten. This study employed a qualitative case study design conducted at TK Aisyiyah 2 Pasui, Enrekang Regency, Indonesia. Data were collected through classroom observations, semi-structured interviews with the principal, teachers, and school staff, and document analysis. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. To ensure research trustworthiness, source triangulation, method triangulation, prolonged engagement, and member checking were applied. The findings reveal that Islamic Religious Education contributes substantially to the development of honesty through the integration of Islamic values into daily learning activities, teacher role modelling, play-based learning, storytelling about the prophets, role-playing, and continuous habituation practices. Collaboration between teachers and parents further strengthens the consistency of honesty education across school and home environments. The study also identifies that authentic behavioural assessment and a supportive religious school culture enhance the internalization of honesty among young children. The study demonstrates that Islamic Religious Education functions not only as a medium for religious knowledge transmission but also as an effective framework for cultivating honesty through developmentally appropriate, experiential, and value-based learning. The findings contribute to the growing literature on Islamic character education by proposing an integrated approach that combines school culture, teacher exemplification, daily habituation, and family engagement to strengthen honesty character development during early childhood.